Exploring miR-30b Methylation and MALAT-1 Expression as Diagnostic Biomarkers for Non-Small Cell Lung Cancer - Marziyeh Memarzadeh; Habib Zarredar; Milad Asadi; Armin Sadeghi; Venus Zafari; Shahryar Hashemzadeh; Hamed Sabbagh-Jadid; Mortaza Raeisi (Middle East Journal of Cancer)
Background: Aberrant methylation and expression of various noncoding RNAs, including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), confer a great potential as tumor markers. This study aimed to investigate miR-30b DNA methylation and metastasis associated lung adenocarcinoma transcript 1 (MALAT-1) expression patterns as potential diagnostic biomarkers for non-small cell lung cancer (NSCLC).Method: In this cross-sectional study, miR-30b DNA methylation and MALAT-1 expression patterns were first explored using microarray data retrieved from the NSCLC dataset in the Cancer Genome Atlas (TCGA)-LUNG. Then, the obtained results were further validated in internal samples. Subsequently, genomic DNA was extracted and modified by sodium bisulfite to determine DNA methylation using q-MSP. Total RNA was extracted and transcribed to cDNA to measure transcription level by quantitative real-time polymerase chain reaction. GraphPad 6 Prism v.8 was used to perform the statistical analyses. Comparisons between groups in internal samples were conducted by paired student's t-test, while Mann-Whitney U test was used to analyze TCGA-LUNG data (P < 0.05).Results: Our results indicated miR-30b hypermethylation, miR-30b downregulation and lncRNA MALAT-1 overexpression in NSCLC tumor samples compared with marginal normal samples. These changes were significantly associated with the stage of malignancy like lymph node metastasis. Also, using receiver operating characteristic curve analysis, MALAT-1 expression, and miR-30b methylation and expression patterns were found as possible diagnostic biomarkers for NSCLC (area under the curve was 0.70, 0.67, and 0.74, respectively).Conclusion: We found involvement of miR-30b hypermethylation and downregulation as well as lncRNA MALAT-1 overexpression with tumor outcomes of NSCLC patients.